Analysis of the Indonesian Government's Actions in Addressing Climate Change from a Legal Perspective - Hisyam Ramadhan (Universitas Muhammadiyah Surakarta, 2024)
Introduction: Climate change has recently become a hot topic of discussion in international forums. As a manifestation of its contribution to addressing climate change and ensuring the fulfillment of its citizens' rights, the Indonesian government, despite ratifying various international agreements related to climate change and devising several strategies, faces a gap between policy commitments and the on-ground reality that indicates a lack of significant impact on climate change. Deforestation, coal usage, and forestry issues have emerged as primary focal points, highlighting the inadequacy of effectiveness in addressing climate change. This research aims to elucidate the extent of the government's commitment to tackling global climate change. The study employs a normative legal method, analyzing related regulations and legal norms through literature review. Secondary data used in this article were obtained through literature review and presented descriptively. Consequently, enhancing inter-agency coordination, strengthening regulations and oversight, and engaging in community education are crucial recommendations to improve the government's effectiveness in responding to the challenges of climate change in Indonesia.